Brand Naming : The Complete Guide to Creating a Name for Your Company, Product, or Service. - Meyerson, Rob. (Business Expert Press, 2021)
This complete and detailed book, Brand Naming, includes insider anecdotes, tired trends, brand origin stories, and busted myths. Whether you need a great name for a new company or product or just want to learn the secrets of professional word nerds, put down the thesaurus--not to mention Scrabble--and pick up Brand Naming.